Transitland : video art from central and eastern Europe 1989-2009 - András, Edit; Ludwig Museum - Museum of Contemporary Art, Budapest (Budapest : Ludwig Museum - Museum of Contemporary Art Budapest, 2009)
McCoy, Kevin ; Bunne, Egon ; Grzinic, Marina ; Smid, Aina ; Vassileva, Mariana ; Hamos, Gusztav ; Solyom, Andras ; Galeta, Ivan Ladislav ; Kovacic, Marko ; Seputis, Gintaras ; Farocki, Harun ; Ujica, Andrei ; Koshkin,Vadim Yuryevich ; SubREAL ; Janczyszyn-Jaros, Anna ; Simic, Mirko ; Shutov, Sergey ; association APSOLUTNO ; Pavlatova, Michaela ; Stubbs, Mike ; Langheinrich, Ulf ; Vangeli, Zaneta ; Rassim ; Grzinic, Marina ; Smid, Aina ; Kaljo, Kai ; Seric-Soba, Nebojsa ; Zbanic, Jasmila ; Sala, Anri ; Steyerl, Hito ; Shkurti, Gentian ; Tomic, Milica ; Mihaltjanu, Dan ; Rossa, Boryana ; Tralla, Mare ; Robakowski, Jozef ; Radek ; Gutov, Dmitri ; Moudov, Ivan ; Abgarian, Sona ; Kovylina, Elena ; Szabolcs, KissPal ; Nikolic, Vladimir ; Ostojic, Tanja ; Ratniks, Martins ; Salmanis, Kriss ; Kruze, Daiga ; Sugar, Janos ; Vassiliev, Yury ; Vujosevic, Natalija ; Acostioaei, Dan ; Braila, Pavel ; Németh, Hajnal ; kuda.org ; Terziev, Krassimir ; Filova, Eva ; Dan, Calin ; Azorro ; Rakauskaité, Eglé ; Sumbadze, Maia ; Machaidze, Nika ; Zet, Martin ; Devic, Goran ; Goba, Kaspars ; Khachatrian, Tigran ; Paci, Adrian ; Niksic, Damir ; Tabatadze, Sophia ; Mavromatti, Oleg ; Xhaferi, Rudina ; Maljkovic, David ; Poljak, Renata ; Rascic, Lala ; Reinigungsgesellschaft ; Rusu, Stefan ; Zmijewski, Artur ; Baladran, Zbynek ; Andjelic-Galic, Gordana ; Fogarasi, Andreas ; Ivanoska, Hristina ; Juice, Khinkali ; Komarov, Aleksander ; Bartana, Yael ; Dawicki, Oskar ; Hakobian, Diana ; Jusic, Adela ; Kameric, Sejla ; Nemes, Csaba ; Norman, Kristina ; Tserakhau, Aliaksei ; Tsulukidse, Natia ; Brogan, Mark ; Chto delat ; Husman, Ana ; Kantor, Istvan ; Richardson, Joanne ; Spasoski, Aleksandar ; Chang, Simon ; Jurica, Ivan ; Kojouharova, Rusiana ; Ivanov, Georgi ; de Montesquion, Eléonore ; etc.
Bibliog. p. 305-310
Publication on the occasion of the exhibition 'Transitland : video art from central and eastern Europe 1989-2009' at the Ludwig Museum - Museum of Contemporary Art in Budapest, 22.01.2010 - 07.03.2010
boek